Clinical outcomes of immunosuppressive therapy for severe aplastic anemia patients with absolute neutrophil count of zero. Issue 1 (1st January 2019) - Liu, Jia; Lu, Xing-Yu; Cheng, Lang; Yang, Yan; Lin, Sheng-Yun; Yin, Hua; Liu, Xiao-Qing; Wu, Xue-Mei; He, Guang-Sheng
ABSTRACT: Objectives: To evaluate the prognosis of adult severe aplastic anemia (SAA) patients with absolute neutrophil count (ANC) values of zero prior to immunosuppressive therapy (IST). Methods: Patients with ANC values of zero prior to IST were separated from very SAA and analyzed in a prospective study. All patients received IST with rabbit anti-thymocyte globulin (ATG) and cyclosporine (CsA). Results: A significantly lower response rate (RR) was identified in patients with ANC = 0 prior to IST when compared to patients with SAA after both 3 and 6 month periods or compared to those with vSAA at 3 months only. The efficacy of IST was inversely related to ANC = 0. The overall survival rate of the 'zero' group was significantly lower than that of the vSAA or SAA groups. Overall survival was closely associated with response to IST, and was inversely related to ANC = 0. Discussion: In SAA patients, ANC is associated with prognosis, the elucidated overall survival improvement in patients without ANC = 0 occurred in conjunction with decreased infection-related mortality. Our study revealed that adult patients with ANC = 0 prior to IST responded poorly to IST, suggesting that having a very low number of neutrophils was a highly predictive factor for efficacy and survival of SAA patients treated with IST. Conclusion: Adult SAA patients with ANC = 0 had a very poor prognosis and new therapeutic regimens may result in better outcome for these patients.